PRO-VESICULAR (PV)-BASED GEL FOR THE TOPICAL DELIVERY OF NAPROXEN: PREPARATION, CHARACTERIZATION AND IN VIVO EVALUATION - Prasad, Vure; T, Saritha.; V Diwan, Prakash; Chenna, Triveni (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective The objective of the present investigation was to develop and characterize a vesicular drug carrier system (Proliposomes) for topical delivery of naproxen to overcome the gastrointestinal complications occurred when taken by oral route. Â Methods Â Proliposomes were prepared by film deposition on carrier method and characterized for size, entrapment efficiency, surface morphology, drug content, percentage yield. Proliposomal gels were prepared by using 1percent carbopol as a polymer and gels were evaluated for PH, viscosity, in-vitro, ex-vivo, pharmacodynmic studies and stability studies. The size and surface morphology were studied using optical microscope and scanning electron microscope. ResultsÂ Â Â Â Â The maximum entrapment efficiency of reconstituted liposomes was 96percent whereas drug content in Proliposomes was found to be more than 90percent. FTIR studies showed no possible interaction between drug and excipients. In-vitro and ex-vivo studies shows that liposomes not only enhance the penetration of drug molecules but also help to localize the drug within the skin indicating sustain release of drug. In-vivo studies concluded that proliposomal gel shows greater percentage of inhibition of paw oedema when compared to marketed gel. Conclusion It was found that Proliposomes exhibited more stability as compared to liposomes. Hence Proliposomes drug delivery system was better choice for sustained release of drug through topical drug delivery. Key words: Naproxen, liposomes, Proliposomes, sustained release, transdermal delivery.